The Gut Viral Metagenome Analysis of Domestic Dogs Captures Snapshot of Viral Diversity and Potential Risk of Coronavirus - Shi, Ying; Tao, Jie; Li, Benqiang; Shen, Xiaohui; Cheng, Jinghua; Liu, Huili (Frontiers in Veterinary Science, 2021)
The close interactions of dogs (Canis lupus familiaris) with humans and surrounding wildlife provide frequent opportunities for cross-species virus transmissions. The co-existence of multiple types of viruses in the reservoir accelerate viral variations. For effective prediction and prevention of future potential viral epidemic or pandemic, the metagenomics method was used to investigate the gut virome status of 45 domestic healthy dogs which have extensive contact with human beings. A total of 248.6 GB data (505,203,006 valid reads, 150 bp in length) were generated of which 46,832,838 reads were de novo assembled into 325,339contigswhichwere best matched with viral proteins available in the NCBI database. In the aggregate, 9834 contigs were confirmed for virus species, accounting for about 3.02% of the total number of contigs. For all the unique contigs, the top 30 ones with the most reads abundance were assigned to DNA virus families Circoviridae, Parvoviridae and Herpesviridae, and RNA virus families Astroviridae, Coronaviridae and Picornaviridae, respectively. Numerous dog virome sequences were homologous to the animal virus of the Astroviridae, Coronaviridae, Circoviridae families, etc.; and phages of the Microviridae, Siphoviridae, Ackermannviridae, Podoviridae, Myoviridae families and unclassified phages. Further, several dog virome sequences had homologous with the insect and plant viruses, which reflects the diet and habitation of dogs. Significantly, canine coronavirus was uniquely identified in all the samples with high abundance, and the phylogenetic analysis therefore showed close relationship with the human coronavirus strain 229E and NL63, indicating the potential risk of canine coronavirus to infect humans by obtaining the ability of cross-species transmission. These results highlight the high frequency of virus detection possible in extensively contacted animal species and provide viral genomes for further disease-association studies, which is meaningful both for the epidemiological and biological elucidation of companion animals and public health.